2016
DOI: 10.1039/c6tc02309f
|View full text |Cite
|
Sign up to set email alerts
|

Cu3Se2 nanostructure as a counter electrode for high efficiency quantum dot-sensitized solar cells

Abstract: Quantum dot sensitized solar cell assembled with a nanostructured Cu3Se2 counter electrode exhibits a high power conversion efficiency of 5.05%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 48 publications
0
11
0
2
Order By: Relevance
“…346 Apart from Cu2S, CuSe or Cu2Se were also applied to fabricate CE in QDSCs. [352][353][354][355][356][357] For example, Cui et al prepared CuxSe/FTO CE through a novel route. 353 They firstly deposited red selenium on FTO by disproportionation of Na2SeSO3 aqueous solution with an ethanol spray and then the red selenium is manipulated as both template and reaction center to fabricate a cuprous embedded CuxSe composite CE upon selenium self-redox reaction with copper ions.…”
Section: Metal Chalcogenidesmentioning
confidence: 99%
See 1 more Smart Citation
“…346 Apart from Cu2S, CuSe or Cu2Se were also applied to fabricate CE in QDSCs. [352][353][354][355][356][357] For example, Cui et al prepared CuxSe/FTO CE through a novel route. 353 They firstly deposited red selenium on FTO by disproportionation of Na2SeSO3 aqueous solution with an ethanol spray and then the red selenium is manipulated as both template and reaction center to fabricate a cuprous embedded CuxSe composite CE upon selenium self-redox reaction with copper ions.…”
Section: Metal Chalcogenidesmentioning
confidence: 99%
“…Tian and coworkers developed a Cu3Se2 CE composed of nanorod arrays and nanosheets, delivering a PCE of 5.05%, higher than the Cu2S/brass based one (4.10%). 354 Wang and coworkers prepared Cu2-xSe nanoparticles and nanowires catalysts by facile wet-chemical methods and then used as CEs in QDSCs. 356 The results showed that Apart from copper chalcogenides based CEs, other binary or alloyed metal chalcogenides, such as PbS, [358][359][360][361][362] CoS, [363][364][365][366] FeS, [367][368][369][370] NiS, 371,372 and Cu2ZnSnS4 (CZTS) or Cu2ZnSnSe4…”
Section: Metal Chalcogenidesmentioning
confidence: 99%
“…Besides, in our previous work [29], CuS layer prepared by chemical deposition method was used as seeds for the Cu3Se2 crystal nucleation. However, due to the nonuniformity of CuS substrate prepared by SILAR method, the substrate was not well covered by Cu3Se2 nanorods, which further limited the catalytic ability of the CE.…”
Section: Introductionmentioning
confidence: 99%
“…Расширение областей использования тонкопленочного селенида свинца в различных устройствах вызывает необходимость развития и оптимизации эффективных технологических приемов его синтеза. В настоящее время для его получения в тонкопленочном состоянии чаще всего используют термическое испарение в вакууме [9], молекулярно-лучевую эпитаксию [10], магнетронное распыление [11], а также гидрохимическое осаждение [12][13][14][15]. Последний из приведенных методов имеет ряд преимуществ, позволяя получать пленки PbSe с вариабельными функциональными свойствами по аппаратурно простой низкотемпературной технологии.…”
Section: Introductionunclassified